Neuroanatomical changes in early Parkinson’s disease with mild cognitive impairment: gray matter and white matter damage - Niu, Yaping; Tan, Changlian; Shen, Qin; Cai, Sainan; Liu, Qinru; Wang, Min; Huang, Congli; Lin, Yiran; Deng, Sinan; Liao, Haiyan (Frontiers in Neurology, 2025)
ObjectivesThis study aims to investigate gray matter (GM) and white matter (WM) changes in early Parkinson’s disease (PD) patients with mild cognitive impairment (PD-MCI) using high-resolution T1-weighted and diffusion-weighted MR images.MethodsWe recruited 40 PD-MCI patients, 26 PD patients with normal cognition (PD-NC), and 40 healthy controls (HC). Voxel-based morphometry (VBM) and surface-based morphometry (SBM) were performed to assess the relationship between gray matter volume, cortical thickness, and cognitive ability. Microstructural white matter changes were evaluated using tract-based spatial statistics (TBSS) with diffusion tensor imaging measures.ResultsWhite matter structural abnormalities were widespread in PD-MCI patients (corpus callosum, corona radiata, superior longitudinal fasciculus, left cerebral peduncle, and left corticospinal tract), with more pronounced involvement in the left cerebral hemisphere compared to healthy controls. Additionally, PD-MCI patients exhibited localized cortical atrophy in the left parieto-occipital region (calcarine, lingual gyrus, and precuneus), left parahippocampal gyrus, fusiform gyrus and entorhinal cortex. A significant positive correlation was observed between reduced gray matter volume (GMV) in the left parieto-occipital region and lower MoCA scores in the PD-MCI group (p < 0.001, R = 0.565).ConclusionEven in early-stage disease, our study demonstrates widespread WM microstructural damage but only subtle GM atrophy in PD-MCI, particularly in the left hemisphere. These findings provide new evidence to enhance our understanding of the pathogenic mechanisms and pathological basis underlying cognitive impairment in Parkinson’s disease.